Facile preparation of a hierarchically porous metal–organic nanocomposite with excellent catalytic performance. Issue 99 (12th October 2016) - Kuang, Rui; Zheng, Luyi; Cottrill, Ethan; Pan, Ning; Chi, Yanhui; Shi, Jingmin; Zhang, Chengcheng; Chen, Xuexue
Abstract : A hierarchical porous MOF nanocrystal, hpCuL (L = 2, 4, 6-tris(3, 5-dicarboxylatephenylamino)-1, 3, 5-triazine) was prepared via a facile gel-aging process. This nanocomposite exhibits high catalytic activity and stability for the reduction of 4-nitrophenol. Abstract : Herein, we report a strategy to prepare a hierarchical micro–meso–macro porous metal–organic nanocomposite, hpCuL (L = 2, 4, 6-tris(3, 5-dicarboxylatephenylamino)-1, 3, 5-triazine), using a facile gel-aging process. The effect of pH values and aging time on the growth morphologies was monitored. This 3-D material, comprised of continuous metal–organic framework nanocrystallines serving as pore walls, exhibits high catalytic activity and stability towards the reduction of 4-nitrophenol by NaBH4 in water.